International monetary system: 1973 reforming in a hurricane - FRIEDMAN, I.S. (PSL Quarterly Review, 2013)
The effort to create a new set of principals for international monetary relations continues, with a deep sense of urgency, but with uncertainty as to what set of principals will best serve the future. International monetary systems should be designed to endure. This requires flexibility and adaptability; it also requires a clear view as to what are the major current and emerging forces in the world economy. The present work examines the history of the international monetary system in order to draw insights as to its future direction. JEL: E42, F33